Strategi Penerjemahan untuk Terjemahan Surat Resmi dari Bahasa Indonesia ke Bahasa Inggris - Dewi, Haru Deliana (Kementerian Sekretariat Negara Republik Indonesia, 2021)
Letter translation is still under-researched until now, while it is important for translators to discover the translation strategies often applied in this text type translation, especially for official letters. In Indonesia official letters are often translated from Indonesian to English, and this paper aims to reveal the translation strategies used in the translation of those official or formal letters. This study analyzes three data of formal letters and their translation by using the descriptive qualitative approach. The results show that official letter translation applies domestication as the translation ideology and the communicative translation as the translation method. To conclude, letter translation is more suitable as target language-oriented translation since letters should be communicative and understandable by the target readers when they are translated. Keywords: Offical letters; letter translation; translation strategies; communicative translation